Processamento digital de imagens de radiografias periapicais sub-expostas aos raios X - Kerbauy, Warley David [UNESP] (1995)
The aim of this study was to evaluate whether digitized images obtained from periapical radiographs taken with low dose of radiation could be improved with the aid of a computer software (PhotoStyler) for digital treatrnent. Serial and standardized radiographs of molar and premolar areas were studied. A total of 57 images equivalent to the radiographs taken with reduced exposure time ( 60 and 80% of the time considered normal), digitized and treated, were submitted to the evaluation of seven exanúners which compared them with those images without treatment. lt was verified that about 80% of the images equivalem to lhe radiographs taken with 60% reduction of ordinary exposure time were considered to having quality for supporting diagnosis. As for the images taken with 80% reduction of ordinary exposure time, about 50% of them were considered suitable for the sarne purpose